PERCEIVED STRESS BY ACTIVE AND SEDENTARY CALL CENTER ATTENDANTS, PARTICIPANT AND NOT PARTICIPANT IN A LABOR GYMNASTICS PROGRAM ABSTRACT (Fiep Bulletin - online, 2015)
The objective of this study was to analyze the level of perceived stress in call center attendants, active, sedentary, participant and not participant of Call Center of a program of Labor Gymnastics (PLG).  The sample was constituted by 90 attendants of Call Center.  The instrument used was the questionnaire of self-evaluation of life style, occurrence and control of stress developed by Andrade (2001) in which are included the questionnaire of habitual physical activities of Pâte, adapted by Nahas (2001), to verify the level of physical activity and the Perceived Stress Scale of Cohen et al. (1983) adapted by Uruhary (1997) to verify the index of perceived stress (ips). The data were treated by descriptive statistics (mean, standard deviation, frequency, percentage) and by inference (Mann-Whitney and “t” test ).  The results indicated that the active attendants participate more of the PLG and present one ips similar to the one showed by the sedentary ones.  The participants of the PLG had not demonstrated differences in the ips when compared with the not participant ones. It is suggested that the PLG participation and the physical activity pratice lead the attendants to self-evaluated herselves less stressed. It was concluded that the labor gymnastics and the life style are related to a better self-evaluation of stress.  It is suggested that as much the methodology of the program how much the enterprise attitude relationed to the physical activity in this company must be reformulated, adapting it to the reality of the employees.
Keywords: stress; labor gymnastics; physical activity.